Epistimology of the 2022 Indonesian Women's Ulama Congress on the Prohibition of the Practice of Female Circumcision from the Perspective of Hakiki Justice - Pratiwi, Anizar Ayu (SMART: Journal of Sharia, Traditon, and Modernity, 2024)
This article analyzes KUPI 2022 recommendation on Female Genitalia Cutting and Injury (P2GP) or female circumcision. Female circumcision is still practiced in various countries including Indonesia, with the excuse of carrying out religious orders for the sake of women's glory and cultural existence. This view is troubling, a form of injustice that continues and has an impact on women, if women are not circumcised then women get a negative stigma. The purpose of this article is what are the reasons why the Indonesian Women's Ulama Congress (KUPI) prohibits the practice of female circumcision? How is female circumcision from the perspective of ultimate justice? This article is a literature research, by examining the KUPI 2022 recommendation on female circumcision as a primary source, then analyzed qualitatively, analyzed based on the theory of ultimate justice. The result of the analysis is that, some scholars view that female circumcision is for the honor of women, but none of the Hadiths that are the basis of female circumcision have reached the level of sahih, and even their position is even dhaif. On this basis, KUPI recommends that female circumcision is prohibited (Haram to be performed) with various considerations. The accusation that if women are not circumcised, their libido and lust will be unstoppable is contrary to the Islamic values of true justice. The contribution of this article is shown for the legislative government to make a policy prohibiting P2GP actions.